Endoplasmic reticulum stress in neurodegenerative diseases - Soto, Claudio (Henry Stewart Talks, 2012)
Neurodegenerative disease, Misfolded aggregates deposited in the brain, Research strategy, Prion diseases, Two conformations of the prion protein, Experimental scrapie model in mice, Upregulation of ER chaperones, ER-stress and UPR in human CJD, PrP interaction with ER chaperones in brain, PrPSc induction of ER-stress and neuronal death, Calcineurin properties, A novel treatment for prion diseases